Estudo da cristalização da frutose em diferentes meios - Silva, Anamaria Teodora Coêlho Rios da (2010)
The phenomena of fructose crystal nucleation and growth in different media, and its water and ethanol/water solubility curves, which were the base of this process, were studied through the fructose crystallization process. The main objective of this work was to study the process of fructose crystallization in solution by partially changing the solvent in attempt to perform a more efficient crystallization. This change was studied by adding ethanol as a fructose anti-solvent and miscible in the solution with the intention of reducing solute solubility. The addition of a second compound to the medium generated the conditions to the fructose effective crystallization. Information that make it possible to improve the control of crystalline product final properties, such as crystal size distribution (CSD) and crystal habit, were obtained from the completion of the present study. The combined method of cooling with anti-solvent addition successfully provided fructose crystallization. The best condition observed in this work was the trial where 66.2 g of fructose were used in 10 g of water and 60 g of added ethanol, because once a lower amount of ethanol was applied, the crystallization occurred in lesser induction time and the yield of 96,8%.